Copper magic - Gibson, Julia Mary (Starscape, 2014)
"The year is 1906, and twelve-year-old Violet Blake unearths an ancient talisman -- a copper hand -- beside the stream where her mother used to harvest medicine. Violet is certain that the copper hand is magic--and if anyone is in need of its powers, it's Violet. Her mother and adored baby brother are gone, perhaps never to return. Her heartbroken father can't seem to sustain the failing farm on the outskirts of Pigeon Harbor, on the shores of Lake Michigan. Surely the magic of the copper hand can make things right for Violet and restore her fractured family. Violet makes a wish. But her ignorant carelessness unleashes formidable powers -- and her attempts to control them jeopardizes not only herself, but the entire town of Pigeon Harbor." --